2016
DOI: 10.18632/oncotarget.11237
|View full text |Cite
|
Sign up to set email alerts
|

Mutational profiling of non-small-cell lung cancer patients resistant to first-generation EGFR tyrosine kinase inhibitors using next generation sequencing

Abstract: Patients with advanced non-small-cell lung cancer (NSCLC) harboring sensitive epithelial growth factor receptor (EGFR) mutations invariably develop acquired resistance to EGFR tyrosine kinase inhibitors (TKIs). Identification of actionable genetic alterations conferring drug-resistance can be helpful for guiding the subsequent treatment decision. One of the major resistant mechanisms is secondary EGFR-T790M mutation. Other mechanisms, such as HER2 and MET amplifications, and PIK3CA mutations, were also reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…23 SOX2 amplification is reported to correlate with resistance to icotinib in EGFR-T790M negative patients. 10,24 However, the impact of the TP53 mutation on resistance to TKIs in this case is unclear.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…23 SOX2 amplification is reported to correlate with resistance to icotinib in EGFR-T790M negative patients. 10,24 However, the impact of the TP53 mutation on resistance to TKIs in this case is unclear.…”
Section: Discussionmentioning
confidence: 88%
“…Primary resistance refers to the immediate inefficacy of EGFR ‐TKIs, while acquired resistance is progression of the disease after a duration of clinical benefit. Acquired resistance to TKIs in patients with advanced NSCLC harboring sensitive EGFR mutations has been well documented; however, knowledge of primary TKI resistance is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor genomic DNA was extracted from formalin-fixed paraffin-embedded (FFPE) sections followed by targeted NGS sequencing as previously described. 9 Sequencing data were mapped onto human hg19, and genomic fusions were identified by using the Fusion and Chromosomal Translocation Enumeration and Recovery Algorithm with default parameters. Total RNA extracted from FFPE sections was subjected to RNA sequencing on the Illumina HiSeq 4000 platform (Illumina, San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
“…In July 2015, FFPE sections of the primary tumor were subjected to comprehensive NGS with a pan-cancer gene panel. 9 The mutation profile showed a rearrangement between chromosome 2 and chromosome 7 with a mutant allele frequency of 11% ( Fig. 2A).…”
Section: Detection Of a Novel Cux1-alk Fusion Gene In A Patient With mentioning
confidence: 99%
“…This irreversible binding of the receptor often leads to more severe on-target side effects like skin rash and diarrhea. A meta-analysis on 3000 patients showed that afatinib has a limited effect on the L858R mutation, whereas it has higher efficacy against the exon 19 deletion [35,36] . The exon 20 insertion also leads to innate resistance against afatinib.…”
Section: First-and Second-generation Egfr-tkismentioning
confidence: 99%